Taking Care of Business in a Male – Dominated Drug Economy: Income Strategies, Risks, and Opportunities of Women Who Use Drugs - Richert, Torkel (Frontiers in Psychiatry, 2022)
Background: Street level drug economies are often described as hierarchical and gender-segregated arenas where men hold high positions and control the supply of drugs, and where women are confined to marginal and low-level positions. Few studies have explored income strategies, risks and opportunities of women who use drugs within drug economies in the Nordic countries. Objective: The aim of this study was to analyze women’s stories about “taking care of business” – making money and securing drugs – in a local drug economy. The study focuses on the women’s gender enactments, the strategies they use to achieve success, and the barriers and risks they face in their everyday endeavors. Methods: This article draws on informal conversations and in-depth qualitative interviews with 27 female drug users in Malmö, Sweden. Results: The interviewed women had established themselves as entrepreneurs in the local drug economy, working hard for their money. However, only a few held middle or high positions, and all women described encountering gendered obstacles and risks in their efforts to take care of business. The patriarchal and sexualized nature of the drug economy meant special prerequisites for the women's income strategies and gender enactments. Three main income strategies were distinguished in the women's stories: 1) using femininity and sexuality, 2) proving tough and dangerous by using street masculinity, and 3) establishing trust, being professional, and keeping a low profile. These strategies involved different advantages and disadvantages, as well as different types of risk. Conclusions: The results show that it is possible for women to achieve success in male-dominated drug economies, but that this is associated with major challenges. Gendered social hierarchies, structures and norms seem to influence the women's gender enactments, opportunities and risks. However, factors such as type of drug use, degree of drug dependence and social situation, was also decisive for their possibility of taking care of business. This points to the importance of combining a focus on gender with a focus on other determants of power relations and vulnerabilities, when studying the everyday lives of people who use drugs.